1968
DOI: 10.1530/jrf.0.0160271
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Progesterone, Testosterone and Ergocornine on Non-Pregnant and Pregnant Guinea-Pigs

Abstract: In guinea-pigs absorbing 0\m=.\1 mg or more progesterone daily from solid, subcutaneous tablets, follicles grow and regress normally as do existing corpora lutea, but ovulation is completely inhibited. The uterus, in the absence of cyclic changes, is continuously stimulated by ovarian oestrogens in progesterone-treated animals. It enlarges, sometimes becoming enormous, and shows various pathological changes.These are absent from the uteri of ovariectomized animals treated with progesterone. Five males which ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1969
1969
1998
1998

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Many ovaries in this series had normal or degenerating follicles of oestrous size, but from the continued inhibition of ovulation, presumably by progesterone (Deanesly, 1968) and from the mucification of the vaginal epithelium up to 116 days after hysterectomy, it appears that the partially regressed corpora lutea are still secreting progesterone. Alternatively, another progestagen may be produced by the lipid-containing interstitial cells during corpora lutea degeneration, as in the rabbit (Hilliard, Spies & Sawyer, 1968).…”
Section: Normal Regression Of Corpora Lutea Of Hysterectomy and The Amentioning
confidence: 70%
“…Many ovaries in this series had normal or degenerating follicles of oestrous size, but from the continued inhibition of ovulation, presumably by progesterone (Deanesly, 1968) and from the mucification of the vaginal epithelium up to 116 days after hysterectomy, it appears that the partially regressed corpora lutea are still secreting progesterone. Alternatively, another progestagen may be produced by the lipid-containing interstitial cells during corpora lutea degeneration, as in the rabbit (Hilliard, Spies & Sawyer, 1968).…”
Section: Normal Regression Of Corpora Lutea Of Hysterectomy and The Amentioning
confidence: 70%
“…In intact guinea-pigs, the daily absorption of 5 mg. progesterone from implants appeared to have no effect on the development, size or survival of cyclic corpora lutea, although ovulation was inhibited (Deanesly, 1968). However, changes in luteal function according to the timing of injections of progesterone have been re¬ ported.…”
Section: Discussionmentioning
confidence: 96%
“…However, the question is whether in other animals and in man prolactin plays a similar essential role in the process of ova implantation as it does in rats. Two studies have indicated that ergocornine is not effective in inhibiting implantation in rabbits (195) and guinea pigs (196). However, a more recent investigation in sows reported that doses of 125-250 mg. of ergocornine can terminate pseudopregnancy in swine with regression of the corpora lutea and reappearance of estrus (197).…”
Section: Nidation Inhibition By Ercot Alkaloidsmentioning
confidence: 99%